(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Black carbon and other selected trace elements concentrations in aerosol samples collected at the Continuous Air Monitoring Station (CAMS) in Chittagong, the second largest city in Bangladesh, were investigated for possible source contributions. The particulate matter (PM) sampling was done from end of winter to middle of rainy season (February and July, 2007) using dichotomous sampler. The samples collected in two fractions of <2.5 ?m (fine) and 2.5 to 10 ?m (coarse) were analyzed for elemental concentrations by proton induced X-ray emission (PIXE), hydrogen by proton elastic scattering analysis (PESA), and black carbon by reflectance measurement. The elemental data sets together with black carbon were analyzed by principal component analysis method to identify the possible sources contributing to the mass concentration of coarse and fine particulate matter (FPM) fractions. The best solutions were found to be six and seven factors for coarse and fine fractions respectively, which could explain more than 90% of the variance in the data set. The sources were identified as biomass burning/brick kiln, soil dust, road dust, Zn source, Pb source, motor vehicle, CNG (compressed natural gas) vehicle and sea salt. It was found that in coarse fraction, the sea salt is mixed with Zn source and in fine fraction, the road dust factor is mixed with CNG vehicle source. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10907 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 19-31, 2012